Comparison of Autogenous vs. Alloplastic Bone Grafts in Mandibular Defect Reconstruction - Qurat Ul Ain, Tariq Javed, Muhammad Bilal, Humna Najeeb, Eram Najm, Sohail Fareed (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Reconstruction of mandibular defects remains a pivotal challenge in maxillofacialsurgery, where the choice between autogenous bone grafts and alloplastic substitutes carries substantial implications for clinical outcomes